A Structural Equation Modeling of the Relationships Between Parenting Styles, Students’ Personality Traits, and Students’ Achievement Goal Orientation - Asanjarani, Faramarz; Aghaei, Khadijeh; Fazaeli, Tahereh; Vaezi, Adnan; Szczygieł, Monika (Frontiers in Psychology, 2022)
Recently, researchers have shown an increased interest in achievement goal orientation correlates. What is not yet clear is the detailed relationships among students’ goal orientation, students’ personality traits, and parenting style. In so doing, this research responds to the need to analyze the importance of parenting styles (permissive, authoritative, and authoritarian) and students’ traits (psychoticism, neuroticism, and extraversion) in explaining the achievement goal orientations (mastery approach, mastery avoidance, performance-approach, and performance-avoidance). In the exploratory correlational study, 586 Iranian students along with their parents were selected as the sample so as to evaluate the structure of the relationships between these variables. The results indicate that students’ psychoticism and neuroticism predict students’ goal orientations (positively: performance and mastery avoidance and negatively: mastery and performance approach) while extraversion did not. Only the authoritative style predicts mastery approach (positively) and psychoticism trait (negatively). Permissive and authoritarian styles do not directly or indirectly predict students’ goal orientations.